ANALISIS & PERANCANGAN SISTEM INFORMASI UKM BERBASIS WEB UNIVERSITAS NASIONAL KARANGTURI - Yonatan, Christopher Nikolas; Abdillah, Muhammad Zakki (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The UKM (Student Activity Unit) information system is one of the supporting factors for the progress of a university, especially for Unkartur (Karangturi National University) which currently requires online UKM data management. This research aims to analyze and design a web-based UKM information system for Unkartur. The author hopes that the interface design resulting from this research will help Unkartur in solving problems regarding the need for online SME data management. The methods used in this research are UML (Unified Modeling Language) and ERD (Entity Relationship Diagram).